2012
DOI: 10.1258/jrsm.2011.110183
|View full text |Cite
|
Sign up to set email alerts
|

Supporting hospital staff to provide compassionate care: Do Schwartz Center Rounds work in English hospitals?

Abstract: SummaryObjective To assess (1) whether the Schwartz Center Rounds ("Rounds"), a multidisciplinary forum which brings together hospital staff to discuss the nonclinical, social and emotional aspects of caring for patients, could transfer from the US to a UK setting; and (2) whether UK Rounds would achieve a similar positive impact on individuals and teams, and hospital culture.Design The results reported are based on 41 qualitative interviews with context provided by additional quantitative research.Setting We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 4 publications
2
84
0
Order By: Relevance
“…The more serious the illness the stronger are the fears and taboos, and one immediate strategy that staff may employ is to distance themselves [10]. Menzies-Lyth [11] has described how people withdraw, perhaps for their own emotional protection, and hide behind an array of organizational mechanisms that offer protection (be this uniforms, procedures, targets, or language).…”
Section: Main Textmentioning
confidence: 99%
“…The more serious the illness the stronger are the fears and taboos, and one immediate strategy that staff may employ is to distance themselves [10]. Menzies-Lyth [11] has described how people withdraw, perhaps for their own emotional protection, and hide behind an array of organizational mechanisms that offer protection (be this uniforms, procedures, targets, or language).…”
Section: Main Textmentioning
confidence: 99%
“…These 1-hour sessions involve the presentation of a case study and discussion of the emotional issues it raised, followed by time for questions, reflection, and the sharing of similar experiences, led by a trained facilitator. 8 A 2012 qualitative analysis of the rounds in two UK pilot sites suggested that rounds increased respect, understanding, and empathy between staff, 8 a benefit that consultant psychologist Leslie Morrison says is beginning to be shown to 'spill over into a greater sense of compassion and empathy for patients'.…”
Section: A Shift Towards True Empathymentioning
confidence: 99%
“…Goodrich (2012) suggests that organisations could facilitate this by providing staff with opportunities to reflect with trusted colleagues either in the form of case consultations, supervision or informal engagement. Establishing valued shared goals is also crucial and organisations could support employees by actively rewarding compassionate attributes and behaviours.…”
Section: Discussionmentioning
confidence: 99%